Development and Characterization of Pullulan-Based Orodispersible Films of Iron - Maram Suresh Gupta; Tegginamath Pramod Kumar; Dinesh Reddy; Kamla Pathak; Devegowda Vishakante Gowda; A. V. Naresh Babu; Alhussain H. Aodah; El-Sayed Khafagy; Hadil Faris Alotaibi; Amr Selim Abu Lila; Afrasim Moin; Talib Hussin (MDPI AG, 2023)
Iron deficiency is the principal cause of nutritional anemia and it constitutes a major health problem, especially during pregnancy. Despite the availability of various non-invasive traditional oral dosage forms such as tablets, capsules, and liquid preparations of iron, they are hard to consume for special populations such as pregnant women, pediatric, and geriatric patients with dysphagia and vomiting tendency. The objective of the present study was to develop and characterize pullulan-based iron-loaded orodispersible films (i-ODFs). Microparticles of iron were formulated by a microencapsulation technique, to mask the bitter taste of iron, and ODFs were fabricated by a modified solvent casting method. Morphological characteristics of the microparticles were identified by optical microscopy and the percentage of iron loading was evaluated by inductively coupled plasma optical emission spectroscopy (ICP-OES). The fabricated i-ODFs were evaluated for their morphology by scanning electron microscopy. Other parameters including thickness, folding endurance, tensile strength, weight variation, disintegration time, percentage moisture loss, surface pH, and in vivo animal safety were evaluated. Lastly, stability studies were carried out at a temperature of 25 °C/60% RH. The results of the study confirmed that pullulan-based i-ODFs had good physicochemical properties, excellent disintegration time, and optimal stability at specified storage conditions. Most importantly, the i-ODFs were free from irritation when administered to the tongue as confirmed by the hamster cheek pouch model and surface pH determination. Collectively, the present study suggests that the film-forming agent, pullulan, could be successfully employed on a lab scale to formulate orodispersible films of iron. In addition, i-ODFs can be processed easily on a large scale for commercial use.